Gamification in Gig Economy for Ride Hailing Drivers in Medan - Shalsabilla Shafira; Ritha F. Dalimunthe; R. Hamdani Harahap (PT FORMOSA CENDEKIA GLOBAL, 2025)
Gamification has become a key strategy used by ride-hailing platforms in regulating and controlling driver behavior through mission elements, points, levels, performance, ratings, challenges and rewards designed to increase driver engagement in work. This study explores in depth how gamification mechanisms affect the working conditions of Gojek and Grab drivers in Medan. The research method used is qualitative with an interpretivist epistemology approach, in-depth interviews with 16 drivers and analyzed with Nvivo12 software. The research findings reveal that drivers face very long working hours with an average of 14 hours per day, while their income is uncertain due to the nature of gig work and gamification mechanisms that prioritize drivers with the highest performance levels. In addition, the work environment is also not entirely safe, given the security risks in Medan and the potential for suspension by the platform based on customer assessments that are often subjective. The gamification system implemented by the platform forms an unequal power relationship between the company and the driver, the platform has great control over the work process, mission access, which has an impact on the driver's income. This creates high work pressure, income uncertainty, and strong dependence on the platform, thus blurring claims of freedom in the gig economy and indicating hidden exploitation. The study also found that bottom-up gamification based on solidarity between drivers can be an alternative solution to create fairer working conditions, although its implementation is still difficult due to internal divisions among Medan drivers. This finding emphasizes the importance of state presence and regulation to eliminate the vulnerability of workers in the gig economy which is further exacerbated by one-sided gamification mechanisms and unequal power relations between platforms and workers.